Caloric Restriction Followed by High Fat Feeding Predisposes to Oxidative Stress in Skeletal Muscle Mitochondria - Crescenzo, R.; Bianco, F.; Coppola, P.; Mazzoli, A.; Liverini, G.; Iossa, S. (Hormone and Metabolic Research, 2013)
The purpose of the present study was to assess the impact of previous period of caloric restriction on energy balance and skeletal muscle mitochondrial energetics in response to high-fat (HF) diet. To this end, 1 group of rats was subjected to 2 weeks of caloric restriction with nonpurified diet and then fed HF diet (430 kJ metabolizable energy/day) for 1 week, while the second group was fed ad libitum with nonpurified diet for 2 weeks and then fed HF diet (430 kJ metabolizable energy/day) for 1 week. Body composition, energy balance, and glucose homeostasis were measured. Mitochondrial mass, oxidative capacity and efficiency, parameters of oxidative stress, and antioxidant defense were evaluated in subsarcolemmal and intermyofibrillar mitochondria from skeletal muscle. Body energy and lipid content, plasma insulin, and metabolic efficiency were significantly higher, while energy expenditure significantly decreased, in food-restricted rats fed HF diet compared to controls. Mitochondrial efficiency and oxidative damage in skeletal muscle were significantly increased, while antioxidant defence was significantly lower in food-restricted rats fed HF diet, compared with controls. Finally, food-restricted rats fed HF diet exhibited significant reduction in subsarcolemmal mitochondrial mass. In conclusion, caloric restriction elicits higher mitochondrial efficiency and predisposes skeletal muscle to high fat-induced oxidative damage, which in turn could lead to impaired glucose homeostasis in food-restricted rats fed HF diet.
Keywords: caloric restriction; mitochondria; high fat diet